Bayu'licious - Bungsu @ Aziz, Dzawin Najaa; Roslan, Nur Farah Adilah; Guriman, Nur Khadijah; Wan Mohd Ridzwan, Wan Mohd Fawwaz (2015)
My name is Wan Mohd Fawwaz Bin Wan Mohd Ridzwan and I am the general manager for Bayu'licious. I am writing to introduce Bayu'licious, where in our company provide canning foods based on Sabahan traditional foods with unique and delicious taste. The main idea is to bring the Sabahan traditional foods to another level in the market. We run the business through manufacturing. The business of canning food is quite regular but our product is unique and never been release before. In addition the product that we produce is different than the other competitors. We spotted our competitors in this type of business and that is Ayam Brand, Yeo's, Adabi who produce canning foods also and well build that has been around for quite a time. Our product consist famous Sabahan traditional foods such as Sinagol, Ambuyat, Hinava, Tuhau, and Serunding Tuhau. Where some of the traditional foods are rare and difficult to find. Now the intention to eat traditional foods of Sabahan are easy to find.